Indoor optical wireless communication - Idrus, Sevia Mahdaliza (Penerbit UTM, 2007)
In lately few years, there has been a rapidly growing in optical wireless communication system for indoor and outdoor applications. Nowadays, the most popular indoor wireless communication is radio frequency (RF) and infrared (IR). Infrared is preferred for many reasons. This article presents an up-to-date review of the optical wireless communication system features for indoor use. There are some explanations on benefit and limitation, advantages and disadvantages, different source of noise, the different possible configuration and finally current and future trends of indoor IR system are visualized. One may see the computer terminals are clustered within office, labs, education institution, libraries and other environments. Due to high cost of reconfiguring and maintaining of wired system, make wireless an economical and flexible alternative to wired systems. Wireless offer flexibility in the placement of terminals and save of time and cost in reconfiguring. IR radiation is a highspeed of indoor wireless communication. The idea of using IR as a medium for indoor communication was first proposed about two decades ago [1,2]. As optical system operates in the near part of spectrum, they use of very low cost optoelectronic components. Usually, these components are small and consume little power,which is very important when manufacturing mobile terminals in large quantities.